The Effect of Scrabble Game toward Students’ Vocabulary Mastery - Alak, Haqul; Mubarok, Husni (Universitas Muhammadiyah Gresik, 2025)
Vocabulary is one of the linguistic aspects that students should master. However the students are difficult in understanding text and lack of vocabulary. As the result, the students have difficulty remembering new vocabulary and do not know the meaning of the words. The aim of this research was to examine the effectiveness of scrabble game on vocabulary mastery of seven grade students at MTs Al-Faizin Guyangan Jepara. This research was quantitative research using Quasi-experimental design with pre-test and post-test design. The population of this research was the seven grade of MTs Al-Faizin Guyangan Jepara. The total of population were 32 students. The sample of the research was VII B as experimental class and VII A 2 as control class. This research used purposive sampling technique to take the sample. To collect the data, researcher used test in the form of multiple choice test for measuring students‟ vocabulary mastery. The researcher conducted data analysis using the T-test. Students in the experimental class had an average score of 65.75, while students in the control class were 59.00. Then, the Sig. (2-tailed) is 0.000, which is less than 0.05, and the T-test is greater than the T-table (-1.517 > 0.468). The results showed that the use of Scrabble game was effective to improve students' vocabulary. This study recommended that the English teacher employ the alternative to increase students' vocabulary mastery.